2019
DOI: 10.1186/s12872-019-1092-5
|View full text |Cite|
|
Sign up to set email alerts
|

Association between plasma lipid levels during acute coronary syndrome and long-term malignancy risk. The ABC-4* study on heart disease

Abstract: Background Emerging evidence suggests that patients with coronary artery disease carry an increased risk of developing malignancy, with deleterious effects on long-term prognosis. Our aim was to ascertain whether baseline plasma lipid levels during acute coronary syndrome (ACS) are associated with malignancy in long-term. Methods This study included 589 patients admitted with ACS to three centers and discharged alive. Plasma lipid levels were assessed on the first morni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to report on the geographic distribution of malignancy in this specific population, ACS patients, with a very long follow-up and very few dropouts. In agreement with the medical knowledge, we found an association between malignancy risk and other important variables, such as age and smoking, but we also found an inverse association between malignancy risk in both urban and rural areas and serum cholesterol as in previous reports [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, the present study is the first to report on the geographic distribution of malignancy in this specific population, ACS patients, with a very long follow-up and very few dropouts. In agreement with the medical knowledge, we found an association between malignancy risk and other important variables, such as age and smoking, but we also found an inverse association between malignancy risk in both urban and rural areas and serum cholesterol as in previous reports [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our different prognostic results support the assumption of the presence of other modifiable risk factors, other than cholesterol levels, that deliberates this risk in the majority of patients and may explain why patients develop myocardial infarction despite a low LDL level 19,39 or why a considerable proportion of major adverse events are still not prevented by aggressive lipid‐lowering treatment 46 . We also observed during the long‐term follow‐up that non‐cardiac death was more prevalent, and an inverse association with plasma lipid levels was observed in concordance with previous reports 5,47,48 . This observation is clinically relevant if we consider that the non‐cardiac mortality rate after acute coronary syndrome has progressively increased in recent years 49,50 .…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that non-CD was more prevalent, 8 and an inverse association with plasma lipid levels was observed in concordance with previous reports. 4,9,10 We could assume that the improvement in cardiovascular treatment tends to reduce cardiovascular mortality, allowing non-cardiac disorders and their complications to prevail. The median age of our cohort at the time of admission was approximately 67 (58–74) years, and it is understandable that the prognostic role of plasma lipids changes with the aging of the population.…”
mentioning
confidence: 99%